2016
DOI: 10.1111/jfr3.12257
|View full text |Cite
|
Sign up to set email alerts
|

An approach for improving flood risk communication using realistic interactive visualisation

Abstract: Floods become disasters when people and property are placed in harm's way. Yet stakeholders, those at risk of flooding, often take no action to reduce their vulnerability. We demonstrated an approach for improving flood risk communication using the process of realistic interactive visualisation. Our goal was to communicate information about flood risk at the community level and increase stakeholders’ intent to take actions to reduce their risk. Realistic visualisation promotes action based on emotional connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
9
0
1
Order By: Relevance
“…While some participants suggested that providing training materials might assist, others were more cautious and thought that tools such as CERA should not be promoted to those without proper training due to high likelihood of misinterpretation. These concerns align with prior research regarding expert users’ concerns with online information being publicly available (eg Morrow et al, 2015; Munroe, Montz, & Curtis, 2018), as well as suggestions that expert‐facilitated interpretation might help laypeople better understand visual risk information (Kuser Olsen et al, 2018).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While some participants suggested that providing training materials might assist, others were more cautious and thought that tools such as CERA should not be promoted to those without proper training due to high likelihood of misinterpretation. These concerns align with prior research regarding expert users’ concerns with online information being publicly available (eg Morrow et al, 2015; Munroe, Montz, & Curtis, 2018), as well as suggestions that expert‐facilitated interpretation might help laypeople better understand visual risk information (Kuser Olsen et al, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…Computational models and visualization tools can support decision‐making in several contexts and timescales, ranging from impending threats of storm surge (Morrow et al, 2015) to long‐term coastal planning for coastal flooding (Kuser Olsen et al, 2018) and sea‐level rise (SLR) (Lindeman et al, 2015). For an imminent threat, storm surge guidance and visualization tools follow the initial detection of a potential hazard (eg hurricane) and support the awareness (sense‐making) of potential future flood hazards to decision‐makers (Kolen & Helsloot, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The resultant map can be used as a tool for risk communication through interactive visualization, for example through an online map running an algorithm on a major government website such as FEMA.gov. Olsen et al [82] proposed a state-of-the-art approach, using realistic interactive visualization to improve flood risk communication. The approach is such that the stakeholders involved in the learning process match the visual representation through awareness, and reflective learning.…”
Section: Coastal Flood Map: Communicating Riskmentioning
confidence: 99%
“…It is therefore vital to communicate the DWF map developed here to people that are directly affected and those making policies for responding to floods. This method will improve significant learning about community-specific flood risk [82] and the ease to take quick action for preparedness, response, recovery and mitigation.…”
Section: Coastal Flood Map: Communicating Riskmentioning
confidence: 99%
See 1 more Smart Citation